Living Biointerfaces for the Maintenance of Mesenchymal Stem Cell Phenotypes. (31st May 2022) - Petaroudi, Michaela; Rodrigo‐Navarro, Aleixandre; Dobre, Oana; Dalby, Matthew J.; Salmeron‐Sanchez, Manuel
Abstract: Living interfaces are established as a novel class of active materials that aim to provide an alternative to traditional static cell culture methods by enabling users to accurately control cell behaviour in a precise, dynamic, and reliable system‐internal manner. To this day, the only reported biointerface has been a coculture between a biofilm of nonpathogenic genetically engineered bacteria and mammalian cells, where the recombinant proteins produced by the bacteria directly influence cell behaviour. In this work, a biointerface is presented between Lactococcus lactis ( L. lactis ) and human mesenchymal stem cells (hMSCs). L. lactis have been engineered to produce human C‐X‐C motif chemokine ligand 12, thrombopoietin, vascular cell adhesion protein 1, and the 7th–10th type III domains of human fibronectin, with the aim of recreating the native bone marrow conditions ex vivo. This active microenvironment has been shown to maintain key hMSC stemness markers, preventing their osteogenic and adipogenic differentiation, and maintaining high stem cell viability and physiological cell‐to‐substrate adhesion dynamics. This work presents proof of concept data that hMSC stemness can be regulated by living materials, using a system based on the symbiotic interaction between different engineered bacteria and mammalian cells. Abstract : Engineered bacteria that express cytokines and growth factors relevant in the bone marrow are used to establish living biointerfaces that allow maintenance of mesenchymal stem cell phenotypes in culture.